Development of Municipal Decision-Making Strategies as Management Tools to Combat Waterborne Diseases - Mangueina, Daniel; Awuah, Esi; Antwi-Agyei, Prince; Ekow Nkwa Sey, Nana (Journal of Air and Water Borne Diseases, 2024)
Waterborne diseases pose a significant global public health threat, particularly in sub-Saharan Africa, where frequent outbreaks occur. These diseases stemming from contaminated drinking water, poor waste management, and insufficient hygiene contribute to high morbidity and mortality in children under 5 years old. A study addressed waterborne diseases in N'Djamena, Chad's 3rd and 9th districts, through decision-making strategies. The research employed various methods, including a household survey using questionnaires, workshops, semi-structured interviews, and focus group discussions. Additionally, documentary research provided essential data for analysing the situation of diseases in the community. Epidemiological data from 2019- 2022 indicated a substantial prevalence of diseases such as diarrhoea, dysentery, skin infections, typhoid, abdominal pain, and malaria, with notable mortality, especially among children. Among surveyed households, 50% believed the consumed water was contaminated, attributing it to faecal matter, while 28% and 22% linked the diseases to inadequate hygiene and unsanitary conditions, respectively. The study advocates for comprehensive strategies, including improving water treatment efficiency, implementing safe waste management, promoting hygiene, and vaccination. Active involvement of all stakeholders, with municipal authorities leading, is crucial for effective implementation and combating waterborne diseases.
Keywords: Chad; districts; N’djamena; strategies; waterborne diseases